Business statistics - Naval Bajpai (Pearson, 2018)
Business Statistics offers readers a foundation in core statistical concepts using a perfect blend of theory and practical application. This book presents business statistics as value added tools in the process of converting data into useful information. The step-by-step approach used to discuss three main statistical software applications, MS Excel, Minitab, and SPSS, which are critical tools for decision making in the business world, makes this book extremely user friendly. This book is highly relevant for students and practising managers